Response of primary mammary epithelial cells to pathogen challenge in dairy cows with divergent genomic breeding values for udder health - Iso-Touru, Terhi; Fischer, Daniel; Panitz, Frank; Taponen, Suvi; Cai, Zexi; Sahana, Goutam; Tapio, Ilma; Vilkki, Johanna (Elsevier, 2025)
This study focuses on the initial cellular response to a causal pathogen in the mammary gland of dairy cows aiming to uncover genomic features associated with mastitis resistance. We analyzed transcriptomes from Escherichia coli -challenged primary bovine mammary epithelial cells derived from milk of cows with high or low genomic index value for udder health. The most striking difference was the markedly higher number of differentially expressed genes post-challenge in the low mastitis resistance group. Gene enrichment analysis indicates a slightly delayed adaptive immune response and early modification of primary metabolic processes in the low mastitis resistance group. Notably, there was no overlap between the DEGs or their potential cis-eQTL with the location of candidate SNPs from association studies of the same cow population. This implies that the genes and pathways involved in the early immune response in the mammary epithelium may not be central for phenotypic mastitis resistance.
Keywords: mastitis; dairy cattle; udder health; transcriptomics; gene networks; eQTL